The influence of aggregate stiffness on the measured and predicted creep behaviour of concrete - Fanourakis, George C (My University, 1998)
Aggregate stiffness is known to influence the magnitude of creep of concrete. The purpose of this research project was to quantify the influence of aggregate stiffness on the measured and predicted long-term creep behaviour of plain concrete. Basic and total creep tests were conducted on concrete specimens of two different strength grades for each of three different commonly used South African aggregate types (quartzite, granite and andesite). In addition, elastic modulus tests Were conducted on cores of the aggregate types considered. The test results revealed that no correlation exists between the creep of concrete and the stiffness of the included aggregate. These results appear to be attributable to the stress-strain behaviour of the aggregate/paste interfacial zone, in the case of aggregates with an elastic modulus in excess of 70 GPa. The experimental basic and total creep values from this investigation were compared with those predicted for each mix at the corresponding ages by the BS 8110 (1985), ACI 209 (1992), AS 3600 (1988), CEB-FIP (1970), CEB-FIP (1978), CEB-FIP (1990) and the RILEM Model B3 (1995). This comparison indicated that the results predicted by each model vary widely and that no correlation exists between the magnitude of the aggregate stiffness and the creep strains predicted by each model.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1998
Keywords: Concrete--Creep; Aggregates (Building materials)